Trastorno de ansiedad generalizada en la fase inicial del tratamiento de hemodiálisis en un paciente - Pazmiño Ramirez, Peter Franklin (2019)
In this case study I have taken into account that the physical state is as important as the mental one since they are both linked, starting from a main objective in which I have studied the generalized anxiety disorder in the initial phase of hemodialysis treatment in a patient, considering Define and detail how the hemodialysis treatment affects the patient with chronic renal failure generating generalized anxiety in the initial phase of the hemodialysis treatment, of the psychology area of the Dial Ríos hemodialysis unit. A 48-year-old female patient who dialyzes on Monday, Wednesday and Friday in the Dial Ríos hemodialysis unit, with a diagnosis of chronic renal failure, this changed her circadian rhythm completely. She lives with her daughter and a niece, in the city of Babahoyo, she is a housewife and has been divorced 15 years ago. He has 5 children, 3 boys and 2 women. Psychological test batteries were applied in order to measure the level of depression and anxiety. A battery of Hamilton's anxiety scale test was applied, which resulted in psychic anxiety: 11 and somatic anxiety: 9 and a Beck test battery: In Beck's depression test, he threw 19, the which is on a scale of. 17-20: Intermittent depression states. It was observed that at the time of the application of the test it was calm, empathic appearance, I collaborate with the test. Therefore, the test results present the patient or user in a state of intermittent depression, in conclusion the level of anxiety was not unfavorable for the patient or user